Persepsi Mahasiswa terhadap Kompetensi Dosen Pendidikan Agama Islam (PAI) Fakultas Agama Islam Universitas Muhammadiyah Kupang - Ade Memeng Tri Putri; Yahya Nikmat Nobisa (Ta lim Jurnal Pendidikan Agama Islam dan Manajemen Pendidikan Islam, 2023)
This study aims to find out the students' perception of the competence of the lecturers in the Islamic Religious Education Program at the Muhammadiyah University of Kupang.This study uses a qualitative method by distributing questionnaires via Google Form to PAI students in the 2019, 2020 and 2021 cohorts, then the data obtained is analyzed using the Percentage Formula.The results of this study include four components of lecturers that have been implemented at Universiti Muhammadiyah Kupang, while there are four components owned by lecturers namely: pedagogical competence, personal competence, social competence and professional competence.The results of the study show that out of all the presentation results, 6 lecturers have been